User Interface Design of Property Sale Application using the Design Thinking Method - Ria Andriani (SCOPUS ID: 57208011426); Muhammad Iqbal Shodikin; Rizki Tri Puji Wanggono (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2023)
The emergence of various new business fields which are dominated by trade is a sign that the Indonesian economy is progressing rapidly, the property business is one example, the property business opportunity is very promising apart from being a place to live, the purpose of people buying property is as an investment. Currently, the tendency of prospective buyers to find information about a property to be purchased is still dominated by brochures, newspapers and other information media such as Facebook, media like this are considered less attractive and less effective because sometimes the information presented is incomplete regarding the specifications of the property. which is available. Based on these problems, this research will design a prototype user interface design for buying and selling and renting property applications with a 360 view using the design thinking method. As for the results of the assessment using SEQ and feedback from respondents getting an average score of 6.4 out of an average passing score of 5.5, the usability testing of the OHome Application prototype can be said to be successful.